PENERAPAN METODE SQ3R UNTUK MENINGKATKAN KEMAMPUAN MEMBACA PEMAHAMAN TEKS DESKRIPSI SISWA KELAS VIIA SMPK SANTA MARIA ASSUMPTA KUPANG - Nenohai, Erna; Margareta, Karus; Makan Malay, Narantoputrayadi (Jurnal Lazuardi, 2025)
This study aims to improve the ability to read comprehension of descriptive texts of class VII A students by applying the SQ3R Methode (Survey, Question, Read, Recite and Reviuw). The type of research used is classroom action research with the following stages, planning, implementation, observation, testing and reflection by taking the research location at SMPK Santa Maria Assumpta Kupang. The subjects in this study were 28 class VII A students. Data collection was carried out using observation and test techniques. The date were processed and analiyzed further using quantitative descriptive. The Result of this study indicate that the application of the SQ3R Methode can improve the ablility to read comprehension of descriptive texts of students where in cycle I the completeness obtained was 43% or 12% students who achieved completeness while those those who had not achieved the completeness criteria werw 57% with a total of 16 students. In addition, there was an increase in the average value of student test results from 65 in cycle II to 81 in cycle II. Thus, the application of the SQ3R Methode (Survey, Question, Read, Recite and Reviuw), has been proven to impove the reading comprehension ablitiy of descriptive texts of class VII A students. This is proven by the increasing student learning outcomes from cycle I to cycle II after the teacher applied the SQ3R Methode.